Cadernos de formação do Pacto Nacional pela Alfabetização na idade certa: convergências e divergências nas concepções de alfabetização - Dal Pizzol, Vanessa (2018)
The National Pact for Literacy in the Right Age (PNAIC), established in 2012 with the objective of institute a commitment between Federal, Federal District, State and Municipal governments to meet goal 5 of the National Education Plan - literate children, at the latest, the third year of elementary school. The research that gave rise to this Dissertation aimed to recognize the conception (s) of literacy present in the proposal of continuing education of literacy teachers that integrates the PNAIC, in particular, the notebooks that served as the basis for this project, the textual contexts in which these conceptions emerge and the role they play there, through the analysis of one of its main instruments, the formation notebooks. It is, therefore, a bibliographical and documentary research, which is also useful for content analysis. The corpus consists of nineteen texts, published in2012 and 2015. The categories of analysis - traditional approach, constructivist approach, historical-cultural perspective, literacy and alphabetic writing system - were elaborated based on authors such as Mortatti (2000, 2006, 2015), Soares (2003, 2010, 2014, 2016), Ferreiro (1990), Ferreiro and Teberosky (1991), Gontijo (2002, 2003) and Morais (2012). The paper presents a synthesis of the historical course of teaching reading and writing in Brazil, favoringthe scenarios of dispute over hegemony among literacy methods; systematizes the context ofemergency of the PNAIC, its structure and functioning, and the main changes that reached it in the six years of its existence. The analysis of the corpus resulted in the following findings: the proposal of continuing teacher training, materialized in the formation notebooks, presents convergences and divergences between the different conceptions of literacy present in the national scenario; the reconstructions performed show inconsistencies with the basic theories, sometimes obscuring them, agglutinating them and proposing approaches that are not consensual inacademics; there is a hodgepodge of ideas, caused by multiple voices present in the different authorship in the texts of formation notebooks, from different institutional linkages; the approach of the alphabetic writing system prevails among the didactic proposals. Reiterating works spread in the area, it is concluded that the program, despite its objective of training literacy teachers in the perspective of literacy and the attempt to recover different traditions of the field, is aligned with a perspective that restrictsliteracy to the domain of the system of alphabetical writing.